Nontrivial solutions of variational inequalities. The degenerate case - Lancelotti, Sergio (Topological Methods in Nonlinear Analysis, 2001)
We consider a class of asymptotically linear variational inequalities. We show the existence of a nontrivial solution under assumptions which allow the problem to be degenerate at the origin.